THE EFFECT OF USING SKIMMING TECHNIQUE ON STUDENTS’ READING COMPREHENSION AT THE ELEVENTH GRADE OF SMAN 1 RANGSANG BARAT KEPULAUAN MERANTI - Indriyani, Syarifah; Yusrida, Yusrida (Journal of English and Arabic Language Teaching, 2025)
Reading comprehension plays a crucial role in English learning. However, the eleventh-grade students at State Senior High School 1 Rangsang Barat, Kepulauan Meranti, still struggled to identify main ideas and detailed information, and comprehensively understand the text. The skimming technique is considered as effective strategy because it allows students to quickly gain an overview of the text and find specific information. This research aimed at finding out the effect of skimming technique on students’ reading comprehension. A quantitative approach was used in this research with pre-experimental one-group pre-test and post-test design. The sample consisted of 26 eleventh-grade students of class 1. Data were collected through multiple-choice test tested its validity and reliability. The results of analysis using descriptive statistics and paired sample t-test showed a significant increase in student reading comprehension. The pre-test mean score 49.54 increased to 72.62 in the post-test. The score of significance of t-test was 0.000 (p<0.05), so H0 was rejected, and H1 was accepted. Thus, the use of skimming technique was proven to have a positive and significant effect on student reading comprehension ability, so it was recommended to be implemented in reading learning at Senior High School level.